2020
DOI: 10.1021/acs.est.9b06150
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Speciation in Atmospherically Deposited Particulate Matter and Implications for Terrestrial Ecosystem Productivity

Abstract: Chemical forms of phosphorus (P) in airborne particulate matter (PM) are poorly known and do not correlate with solubility or extraction measurements commonly used to infer speciation. We used P X-ray absorption near-edge structure (XANES) and 31 P nuclear magnetic resonance (NMR) spectroscopies to determine P species in PM collected at four mountain sites (Colorado and California). Organic P species dominated samples from high elevations, with organic P estimated at 65−100% of total P in bulk samples by XANES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…However, the contributions of those sources to P org in the Puerto Rico dust are lower than those in the dust collected above the Mediterranean Sea and Panama during drying season, which had much higher P org concentration . High organic P concentrations were also observed in the aerosols that were collected at mountainous sites and had a high contribution of biogenic P …”
Section: Resultsmentioning
confidence: 86%
“…However, the contributions of those sources to P org in the Puerto Rico dust are lower than those in the dust collected above the Mediterranean Sea and Panama during drying season, which had much higher P org concentration . High organic P concentrations were also observed in the aerosols that were collected at mountainous sites and had a high contribution of biogenic P …”
Section: Resultsmentioning
confidence: 86%
“…Compared with Figure S5 , the P chemical shift of sample 5 largely shifts to the left as the pH increases. According to the reference [ 17 ], it can be confirmed that sample 1 is DPD, sample 5 is DPM. The phosphoric ester was partially hydrolyzed under alkaline conditions, protonated into free phosphoric acid [ 18 ], and then reacted with sodium hydroxide to neutralize the acid and alkali; and the deprotonation formed Na 3 PO 4 (11.477), Na 2 HPO 4 (10.492) and NaH 2 PO 4 (8.669).…”
Section: Resultsmentioning
confidence: 99%
“…Our finding that clinal increases in dust P concentrations spiked during our second sampling year suggests that this dust may have exerted ecosystem-level influences at high elevations. Previous studies have illustrated greater airborne flux of bioavailable P delivered to high elevation sites, with implications for terrestrial ecosystem productivity ( O’Day et al, 2020 ). In this slowly eroding, dust-reliant montane ecosystem, dust-associated mineral P contributions elicit transformative effects on vegetation communities, soil and ecosystem development, and biogeochemical cycling ( Arvin et al, 2017 ; Gu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%